PURIFICATION OF BIOACTIVE COMPOUNDS PRODUCED BY BREVIBACILLUS LATEROSPORUS SA14 AND ITS ANTI-MRSA ACTIVITY - K. CHAWAWISIT; M. LERTCANAWANICHAKUL (International Journal of Pharma and Bio Sciences, 2014)
An antimicrobial peptides (AMPs)- producing strain, Brevibacillus laterosporus SA14, has been isolated from air. The corresponding AMPs were purified from 4-day culture supernatant to homogeneity by 50% saturated ammonium sulfate precipitation, sequential SP-Sepharose Fast Flow and C18 reverse-phase high performance liquid chromatography. The final purification step, three active fractions were harvested at retention time about 22.90, 23.20 and 26.30 min, designated as SA14-A, SA14-B and SA14-C, respectively. The three AMPs showed antibacterial activity against fifty clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) which had the specific activity of about 300 AU/ml. In this study, the bioactive compounds that produced by B. laterosporus SA14 contained AMPs which are medically important substances may be used for alternative treatment of MRSA infection if it has been additionally studied to cytotoxicity against normal human cell.